2015
DOI: 10.1353/bsr.2015.0011
|View full text |Cite
|
Sign up to set email alerts
|

Our Village Is Watching: Sociocultural and Attitudinal Factors Related to HIV Sexual Risk Behaviors among Black South African Men Who Have Sex with Men

Abstract: The aim of this study is to explore the attitudes, cultural norms, and social factors among South African black men who have sex with men (msm) residing in the Eastern Cape in the context of hiv sexual risk behavior. Data were collected from demographic questionnaires and six focus group discussions with 41 men residing in the cities of East London and Port Elizabeth, Eastern Cape Province, South Africa. Participants were in agreement that many black South Africans in their locality view homosexuality as somet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…This means that HIV prevention efforts developed in urban contexts may need to be adapted based on the relative importance of particular risk factors. Potentially important features of the rural context that may affect HIV risk among MSM include: the relative importance of traditional cultural beliefs and practices (Icard et al, 2015); high rates of poverty and unemployment (Neves & du Toit, 2013;Pronyk et al, 2008); high levels of circular migration between urban and rural areas (Hunter, 2010;Neves & du Toit, 2013;Pronyk et al, 2008); and lower levels of educational attainment (Lane et al, 2014). Based on findings among urban and peri-urban MSM, the relatively higher rates of rural unemployment, and lower levels of formal education in rural South Africa may have a disproportionate effect on HIV risk among MSM in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…This means that HIV prevention efforts developed in urban contexts may need to be adapted based on the relative importance of particular risk factors. Potentially important features of the rural context that may affect HIV risk among MSM include: the relative importance of traditional cultural beliefs and practices (Icard et al, 2015); high rates of poverty and unemployment (Neves & du Toit, 2013;Pronyk et al, 2008); high levels of circular migration between urban and rural areas (Hunter, 2010;Neves & du Toit, 2013;Pronyk et al, 2008); and lower levels of educational attainment (Lane et al, 2014). Based on findings among urban and peri-urban MSM, the relatively higher rates of rural unemployment, and lower levels of formal education in rural South Africa may have a disproportionate effect on HIV risk among MSM in these areas.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the most effective method of service administration to sub-Saharan MSM has been raised as a research priority by previous studies. 12 As stigma and discrimination have been identified as prevalent barriers to care for South African MSM, 11,13,[20][21][22] determining operative methods of overcoming these barriers is essential to establishing optimally accessible services. Clients and providers in both cities highly ranked confidentiality of visit, and friendly staff among ideal clinic characteristics, indicating that there is already mutual understanding in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…[20][21][22] These barriers include the heterosexual focus of public health strategies for HIV prevention, which ultimately isolate MSM from services 13,22 as well as the stigmatizing views of some providers regarding MSM, which is compounded by limited training regarding sexual health of MSM. 11,13,[20][21][22] Men who have sex with men face high levels of social stigma and homophobic violence which may be associated with traditional attitudes toward sexuality. 23,24 A 2013 study found that less than a third of South Africans reported that homosexuality should be accepted by society.…”
Section: Introductionmentioning
confidence: 99%
“…The participants' accounts of avoidance attests to the avoidance strategy that many gay men fearful of homophobic violence engage in (Almeida, Johnson, Corliss, Molnar and Azrael 2009;Icard et al 2015;Jacques 2014;Plant, Zielaskowski and Buck 2014;Skinta, Brandrett, Schenk, Wells and Dilley 2013). Strategies of avoidance of avowed physical spaces or social spaces where one's sexuality is considered problematic can be read as a survival strategy that enables the individual to maintain a sense of well-being, both physically and mentally.…”
Section: Survival Strategies Avoidancementioning
confidence: 98%
“…Part of the heteronormative assumptions is the belief that opposites attract within a binary sexed and gendered lens whereby only men and women exist and are attracted to each other (Kitzinger 2005a(Kitzinger , 2005b. Such a belief reinforces the prejudice and violence that characterises many practices of homophobia (Arfer and Eaton 2013;Arndt and De Bruin 2006;Hames 2011;Icard et al 2015;Lee and LaDousa 2015;Nduna and Mavhandu-Mudzusi 2015;Rich 1980;Schilt and Westbrook 2009). …”
Section: Theoretical Overview and Conceptual Frameworkmentioning
confidence: 99%